2013
DOI: 10.1002/ijc.28037
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS4 and its proteolytic fragments differentially affect melanoma growth and angiogenesis in mice

Abstract: The metalloproteinase ADAMTS4 (ADAMTS, a disintegrin-like and metalloproteinase with thrombospondin motif)/aggrecanase-1 is highly expressed in cartilage and has been implicated in human arthritis. Although abundantly expressed in many types of cancer, its role in cancer remains unknown. In this work, we demonstrate for the first time that full-length ADAMTS4 and its catalytically more active N-terminal 53 kDa autocatalytic fragment both promote B16 melanoma growth and angiogenesis in mice. In contrast, overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 32 publications
4
37
0
1
Order By: Relevance
“…Combined with the clinical follow-ups, we identified the overexpressed ADAMTS4 as a crucial factor in CRC progression. Consistently, the overexpressed prolife of ADAMTS4 has been reported in several cancers including glioblastoma [25], head and neck cancer [26], melanoma [27], and epithelial ovarian cancer [12]. By immunochemical analysis of a CRC tissue microarray, we confirmed that ADAMTS4 expression was elevated in CRC tissues compared to normal tissues and predicted a poor prognosis in CRC.…”
Section: Discussionsupporting
confidence: 63%
“…Combined with the clinical follow-ups, we identified the overexpressed ADAMTS4 as a crucial factor in CRC progression. Consistently, the overexpressed prolife of ADAMTS4 has been reported in several cancers including glioblastoma [25], head and neck cancer [26], melanoma [27], and epithelial ovarian cancer [12]. By immunochemical analysis of a CRC tissue microarray, we confirmed that ADAMTS4 expression was elevated in CRC tissues compared to normal tissues and predicted a poor prognosis in CRC.…”
Section: Discussionsupporting
confidence: 63%
“…C-terminal processing of the full-length ADAMTS-4 has been also reported in synovium and cartilage (15,(57)(58)(59). Recently, Rao et al (44) reported that proteolytic fragments of ADAMTS-4 containing only the C-terminal non-catalytic domains are found in cultured cells and human cancer tissues and suppress melanoma cell growth and angiogenesis in mice. Thus, processing of these domains is likely to have a large impact on the function and trafficking of ADAMTS-4 in vivo.…”
Section: Discussionmentioning
confidence: 85%
“…Because LRP1 is widely expressed in a variety of organs, we speculate that endocytic regulation of ADAMTS-4 activity occurs in various other tissues. The expression of ADAMTS-4 and ADAMTS-5 mRNAs has been reported to increase in human glioblastomas (41)(42)(43) and ADAMTS-4, and its proteolytic fragments differentially affect melanoma growth and angiogenesis in mice (44). Interestingly, ADAMTS-4 pro- motes neurite outgrowth by cleaving proteoglycans, which contributes to functional recovery after spinal cord injury (45).…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, ADAMTS4 seems to have double-edged functions. When inactive -still carrying the propeptide -ADAMTS4 exhibits anti-tumorigenic features which is reversed upon propeptide cleavage [36].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of ADAMTS4 has been associated with melanoma growth and angiogenesis in mice [36]. ADAMTS4 is activated by MT4-MMP [24].…”
Section: Discussionmentioning
confidence: 99%